EFEKTIVITAS LATIHAN AD – MENSTREN DALAM MENINGKATKAN KETAHANAN MENTAL PADA ATLET CRICKET MUARO JAMBI - Sulaiman; Grafitte Decheline; Mohd Adrizal (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Mental toughness is one of the important factors that influences athletes’ performance during training and competition. Based on observations, Cricket athletes in Muaro Jambi still experience pre-competition anxiety, characterized by nervousness, trembling, excessive sweating, and fear of facing opponents perceived as stronger. These conditions may negatively affect athletes’ performance during competitions. This study aimed to determine the effectiveness of Ad-Menstren training in improving the mental toughness of Cricket athletes in Muaro Jambi. The study employed an experimental method using a One-Group Pretest–Posttest Design. The sample consisted of 15 Cricket athletes from MuaroJambi selected through a total sampling technique. Data were collected using a mental toughness scale. Data analysis was conducted using the Shapiro–Wilk normality test and the Paired Sample t-test at a significance level of 0.05. The results showed that the average mental toughness score increased from 49.53 in the pretest to 67.53 in the posttest. The normality test indicated that the data were normally distributed, with significance values of 0.412 for the pretest and 0.304 for the posttest. Furthermore, the hypothesis test revealed a significance value of 0.001 (< 0.05) and a t-value of 4.475, which was greater than the t-table value of 1.7709. These findings indicate that Ad-Menstren training is effective in improving the mental toughness of Cricket athletes in Muaro Jambi.